PENGARUH ENVIRONMENTAL, SOCIAL AND GOVERNANCE DISCLOSURE TERHADAP FINANCIAL PERFORMANCES (Studi Empiris pada Perusahaan Non-Keuangan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Ignatius Alan Yudha Pradana; Herry Laksito (Diponegoro Journal of Accounting, 2023)
This study aims to examine the effect of environmental, social and governance disclosure on return on assets, return on equity and market value. Tests in this study use environmental, social and governance disclosure as an independent variable, as well as return on assets, return on equity and market value as the dependent variable. The samples tested in this study are non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. Samples obtained using purposive sampling as a sampling method based on certain criteria. The analytical method used is Partial Least Square (PLS) with WarpPLS software version 7.0 as an auxiliary application. The research obtained results showing that environmental, social and governance disclosure has a significant positive effect on return on assets, return on equity and market value.